2019
DOI: 10.1039/c9sc02359c
|View full text |Cite
|
Sign up to set email alerts
|

Steric and electronic control of an ultrafast isomerization

Abstract: Synthetic control and the influence of steric and electronic factors on the ultrafast (picosecond) isomerization of penta-coordinate ruthenium dithietene complexes (Ru((CF3)2C2S2)(CO)(L)2, where L = a monodentate phosphine ligand) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 40 publications
4
5
0
Order By: Relevance
“…Isomers , 6 ( III L U P P P P ), , 10 ( III L U P P P M ), and 12 ( III L U P M P M ) have an equatorial CO with the alternative ruthenium stereochemistry III . The calculated average C–C and C–S bond distances for all the isomers ( 1 – 12 ) of 1.377 and 1.735 Å, respectively (Figure ), are in good accord with the dithiolate (two electron-reduced) character of the ligand (C–C and C–S bond distances of 1.337 and 1.761 Å), which yields a Ru­(II) d assignment for all the isomers 1 – 12 , in excellent agreement with the experiment …”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Isomers , 6 ( III L U P P P P ), , 10 ( III L U P P P M ), and 12 ( III L U P M P M ) have an equatorial CO with the alternative ruthenium stereochemistry III . The calculated average C–C and C–S bond distances for all the isomers ( 1 – 12 ) of 1.377 and 1.735 Å, respectively (Figure ), are in good accord with the dithiolate (two electron-reduced) character of the ligand (C–C and C–S bond distances of 1.337 and 1.761 Å), which yields a Ru­(II) d assignment for all the isomers 1 – 12 , in excellent agreement with the experiment …”
Section: Resultssupporting
confidence: 83%
“…In a previous study, three ν CO bands near 1980, 1960, and 1940 cm –1 were observed in solution . DFT calculations show that the scaled ν CO frequencies for isomers 1 (1957 cm –1 ), 4 (1956 cm –1 ), 9 (1955 cm –1 ), 11 (1954 cm –1 ), and 12 (1954 cm –1 ) are in good agreement with the experimentally observed ν CO band at 1960 cm –1 , as are the scaled ν CO frequencies for isomers 2 (1940 cm –1 ), 3 (1942 cm –1 ), 5 (1943 cm –1 ), and 8 (1939 cm –1 ) with the reported ν CO band near 1940 cm –1 .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…This strong affinity originates from the soft–soft interaction between the C- and P-donors with platinum and helps in the formation of kinetically inert bonds, which inhibit ligand dissociation and slow the formation of highly electrophilic complexes that may otherwise induce undesirable effects as these complexes react indiscriminately with biological molecules . Substituents on both NHCs and phosphines can also be modified readily so as to fine-tune the extent of steric interaction with other ligands around the coordination sphere of platinum …”
Section: Introductionmentioning
confidence: 97%